Why do we observe significant differences between measured and ‘back-calculated’ properties of natural fibres? - Shah, Darshil U.; Nag, Ranajit K.; Clifford, M.J. (Springer, 2016)
The drive towards sustainability, even in materials technologies, has fuelled an increasing interest in bio-based composites. Cellulosic fibres, such as flax and jute, are being considered as alternatives to technical synthetic fibres, such as glass, as reinforcements in fibre reinforced polymer composites for a wide range of applications. A critical bottleneck in the advancement of plant fibre composites (PFRPs) is our current inability to predict PFRP properties from data on fibre properties. This is highly desirable in the cost- and time-effective development and design of optimised PFRP materials with reliable behaviour. This study, alongside limited other studies in literature, have found that the experimentally determined (through single fibre tests) fibre properties are significantly different from the predicted (‘backcalculated’ using the popular rule-of-mixtures) fibre properties for plant fibres. In this note, we explore potential sources of the observed discrepancy and identify the more likely origins relating to both measurement and errors in predictions based on the rule of-mixtures. The explored content in this discussion facilitates the design of a future investigation to (1) identify the sensitivity of the discrepancy between measured and predicted fibre properties to the various potential origins, (2) form a unified hypothesis on the observed phenomenon, and (3) determine whether the rule-of-mixtures model (in specific cases) can be improved and may be able to predict properties precisely.